A simple method to design a tri-bandpass filter using open-loop uniform impedance resonators. Issue 1 (2nd January 2020) - Weng, Min-Hang; Hsu, Che-Wei; Lin, Yuanmo; Tsai, Chin-Yi; Yang, Ru-Yuan
ABSTRACT: The paper presents a simple method to design a tri-band bandpass filter (BPF) using only two pairs of open-loop uniform impedance resonators (OLUIRs). The three passbands can be designed independently by selecting the lengths of two pairs of the OLUIRs. The design procedure is described in this paper. A tri-bandpass filter example is designed at 1.93, 2.6 and 3.9 GHz that can be applied to digital enhanced cordless telecommunications (DECT) and worldwide interoperability for microwave access (WiMAX). By means of the cross-coupling effect with different coupling paths, several transmission zeros appear near the passbands, thus enhancing the selectivity of the passbands. The measured results of the fabricated tri-BPF match the simulated results and confirm the design concept.